ANALISIS KUALITAS PELAYANAN PASIEN RAWAT INAP PADA RUMAH SAKIT KHUSUS IBU DAN ANAK ANNISA BANJARMASIN - Sri Mulyani; Ni Nyoman Suarniki; Fatimah - (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2018)
Abstract, This reseach aims to analyze the quality of services measured by reliability, reliability, responsiveness, assurance, emphaty, tangibles at the maternal and child hospital of annisa banjarmasin. The research method used is descriptive method. The population of this study is all inpatients at the Maternal and Annisa Special Hospital in 2016 which amounted to 960 people. Samples taken are as many as 100 people. The conclusions of this study are the services that should be improved on the services of reliability ie doctors, nurses and hospital personnel must arrive on time, especially the schedule of doctor's arrival that does not change so that does not make patients wait. Aspects of responsiveness ie doctors should give longer time to consult and explain in detail the treatment solution that will be given to the patient. Aspect tangibles the hospital should pay attention to the location of the parking for comfort and safety of patients and families.